2013
DOI: 10.12968/bjon.2013.22.sup15.s46
|View full text |Cite
|
Sign up to set email alerts
|

Hand burn management: minimising pain and trauma at dressing change

Abstract: The aim of wound management in hand burn injuries is to restore function and prevent problem scars, so a key consideration in wound healing is the removal of dressings without causing pain and further trauma as well as preserving function. Conventionally, wound dressings such as paraffin gauze were used for burn injuries, but this led to pain and trauma on removal, as well as drying out. This study looks at the use of Mepitel® One on hand burns; this dressing incorporates all the benefits of Mepitel, however, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…This allows movement, protects the burnt skin from contamination, facilitates visual assessment of the skin, and minimizes the frequency of dressings. However, edema and maceration often occur, and patients occasionally find these unsightly 128 . Gore-tex bags are semipermeable, reusable, and theoretically provide a superior healing environment to polythene, with less maceration.…”
Section: Resultsmentioning
confidence: 99%
“…This allows movement, protects the burnt skin from contamination, facilitates visual assessment of the skin, and minimizes the frequency of dressings. However, edema and maceration often occur, and patients occasionally find these unsightly 128 . Gore-tex bags are semipermeable, reusable, and theoretically provide a superior healing environment to polythene, with less maceration.…”
Section: Resultsmentioning
confidence: 99%
“…6 , 7 Pain control was presented as a challenge for surgeons, especially for pain-related dressing change. 8 Moreover, another important challenge is coexisting anxiety, which is particularly obvious during the first dressing change. 9 It has been reported that anticipation of pain exacerbates patient anxiety, which in turn can exacerbate the pain.…”
Section: Introductionmentioning
confidence: 99%
“…Dressing the hand with appropriate wound covers should minimise the level of pain, prevent the formation of scar contractures and guarantee the largest possible functionality. Conventional wound dressings such as paraffin gauze do not meet the above criteria for the treatment . It is believed that skin grafting of partial‐thickness wounds offer positive clinical effects in 97% of patients with superficial wounds of the hands and in 81% of patients with deep wounds.…”
Section: Introductionmentioning
confidence: 99%